A Bioinformatics approach to designing a Zika virus vaccine. (June 2017) - Dey, Sumanta; Nandy, Ashesh; Basak, Subhash C.; Nandy, Papiya; Das, Sukhen
Graphical abstract: Fig. 3 Profiles of average solvent accessibility (blue) in% and amino acid sequence variability (red) in numbers of the 60 Zika envelope protein fragments plotted against amino acid numbers. The short horizontal green lines are identified segments of the sequences where the amino acids are most conserved and have highest solvent accessibility. A method is presented to determine highly conserved, surface exposed peptides on the envelope protein with good epitope potential as starting points for a rationally designed peptide vaccine against the Zika virus. Highlights: Zika virus envelope gene and protein sequences analysed. Based on maximum sequences available, identified peptide segments with minimum variability and maximum surface accessibility using alignment-free numerical characterization techniques. Checked identified regions on 3D crystal structures to ensure solvent accessibility. Confirmed linear and conformational epitope potential of identified segments using web based servers. These peptide regions are suggested as starting points for rational design of peptide vaccines subject to wet lab verification. Abstract: The Zika virus infections have reached epidemic proportions in the Latin American countries causing severe birth defects and neurological disorders. While several organizations have begun research into design of prophylactic vaccines and therapeutic drugs, computer assisted methods with adequate data resources can be expected to assist in these measures to reduce lead times through bioinformatics approaches. Using 60 sequences of the Zika virus envelope protein available in the GenBank database, our analysis with numerical characterization techniques and several web based bioinformatics servers identified four peptide stretches on the Zika virus envelope protein that are well conserved and surface exposed and are predicted to have reasonable epitope binding efficiency. These peptides can be expected to form the basis for a nascent peptide vaccine which, enhanced by incorporation of suitable adjuvants, can elicit immune response against the Zika virus infections.